Both Ethnic and Religious: Explaining Employment Penalties Across 14 Ethno‐Religious Groups in the United Kingdom. Issue 3 (23rd November 2015) - Khattab, Nabil; Modood, Tariq
Abstract : This article uses the case of the probability of being in employment among different ethno‐religious groups in Britain over a period of 12 years (2002–2013) to illustrate how different degrees of labor market penalty in the United Kingdom are highly associated with the different processes of racialization they undergo in the United Kingdom. It is argued that what matters in producing the observed inequalities in the United Kingdom is the inescapable centrality of "color" (mainly blackness) and "culture" (particularly being Muslim) and the way different Muslim and black groups have been racialized. The findings of this study leave little doubt that there is a black and a Muslim penalty in the labor market, but at the same time it suggest that these penalties are not fixed but tend to vary in extent and nature.